The Effect of Body Mass Index on Bleeding After on Pump Coronary Artery Bypass Grafting - Siddiqeh, Musfireh; Khan, Imran; Fayyaz, Fakher-e-; Dawood, Muhammad Awais; Hasan Kirmani, Syed Muzaffar; Khurshid, Hannah; Javaid, Rehana (Pakistan Armed Forces Medical Journal, 2022)
Objective: To study the relationship of body mass index (BMI) and postoperative bleeding in patients undergoing isolated coronary artery bypass grafting (CABG) using cardiopulmonary bypass (CPB). Study Design: Analytical cross sectional study Place and Duration of Study: Cardiothoracic services, Almana General Hospital, Al Khobar, Saudi Arabia, from Oct 2019 to Oct 2021. Methodology: Two hundred and twenty (220) consecutive patients who underwent CABG using cardiopulmonary bypass were included in the study. Patients who had additional procedures, those who were operated in emergency and those with significant comorbidities like hepatic and liver dysfunction were excluded from the final analysis. Patients were divided into three groups according to their BMI, healthy weight (BMI 18.5 to <25), overweight (BMI 25 to <30) and obese (BMI >30). The world health organization (WHO) definition was used to define different categories of BMI. Various perioperative variables were recorded for all the patients. Only the immediate postoperative follow up period was included in the study. Data was analyzed using IBM SPSS-statistics 23.0 (IBM, SPSS Inc., Chicago, IL). Results: Of the 220 patients included in the study, 184(83%) were male patients and 36(16%) female patients. There was no significant difference in the mean age of the patients in the three groups (p=0.481). There were significantly more hypertensive patients 46(45%) in the overweight group compared to other two groups (p=0.025). Baseline diabetic status was not significantly different among the three categories (p=0.978). Total mediastinal drainage in the first 24 hours was significantly less in the obese group (3.7±4.45 ml) compared to overweight (4.4±2.7 ml) and healthy weight (7.35±8.5 ml) patients (p=0.001). There was no mortality in the studied cohort. Conclusion: Bleeding after isolated coronary artery bypass grafting is inversely related to BMI. Patients with healthy and overweight BMI are at higher risk of bleeding compared to obese patients.